Accountability in governance: will and can traditional village-owned enterprises achieve it? - Aprina Nugrahesthy Sulistya Hapsari; Intiyas Utami; Yohanes Werang Kean (STIE Perbanas Surabaya, 2020)
Village-Owned Enterprise (in Indonesia commonly referred to BUMDes) has a goal to develop the economy of the village community. Wologai Tengah Vil-lage in Ende Subdistrict, Flores Regency, East Nusa Tenggara Province, Indo-nesia is one of the traditional villages that have a tourist attraction, especially in terms of traditional houses and various rituals. One of the advantages of Wologai Tengah Village is the ability of its traditional leaders (Mosalaki) and village officials to mobilize village communities. This research aims to explore the understanding of village officials and traditional leaders in realizing the village accountability and the philosophical value of local wisdom of traditional village by supporting the accountability of BUMDes. The qualitative research method was selected in this study with informants consisting of traditional leaders, village officials, government representatives, and local village communities. Data were obtained through direct interviews and Focus Group Discussion attended by resource persons related to the BUMDes. In terms of village accountability, traditional leaders and village officials have a strong will in preparing financial reports and budget of BUMDes. The problem faced in realizing village accountability is the inadequate capacity of human resources to prepare financial reports and budgets of BUMDes.